Advances in the economic analysis of participatory and labor-managed firms. Vol. 12 - DeVaro, Jed (Emerald, 2011)
This 12th edition of Advances in the Economic Analysis of Participatory and Labor-Managed Firms contains a stimulating collection of original papers spanning a wide variety of topics. Part 1 of the volume contains three papers on the subject of job design and organizational performance, covering the determinants of multiskilling from a theoretical perspective and also the empirical effect of multiskilling and teams on financial performance. Part 2 of the volume concerns compensation, worker attitudes, and productivity. Papers in this section cover the effect of rules and costs on employer-provided health insurance, majority ownership and executive compensation, worker attitudes towards different forms of employee ownership and variable pay, and an analysis of performance-related pay, unions, and productivity in Italy. Part 3 contains three studies of worker cooperatives and nonprofit organizations in Italy, Spain, and Uruguay. The volume concludes with a debate on free trade and the ecological effects of alternative socio-economic systems.
Keywords: Management -- Employee participation.; elektronické knihy; electronic books